SINDANG IN HISTORICAL PERSPECTIVE: THE CONSTRUCTION OF TERRITORY AS LINGUISTIC IDENTITY: Sindang dalam Tinjauan Historis: Kontruksi Wilayah sebagai Identitas Linguistik - Berlian Susetyo; Krisnaldi Dwinanda (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines the historical processes that shaped the Sindang language as a linguistic identity of the Sindang community. Grounded in the understanding that a territory is not merely a geographical space but also a determinant of linguistic identity, this research combines historical methods with a linguistic approach to interpret the Sindang language as a socio-cultural product formed through the collective experiences of its speakers. The historical method is applied through the stages of heuristics, source criticism, interpretation, and historiography to reconstruct the dynamics of the Sindang region, including administrative changes, the formation of marga (clan) structures, and the influence of colonial policies. The linguistic approach complements this analysis by examining the features of the Sindang language, its distribution, and its relationship with surrounding speech communities, highlighting how social interactions contribute to linguistic identity formation. The novelty of this research lies in its specific focus on linking the historical development of the Sindang region with the emergence of its linguistic identity. To date, no study has systematically analyzed the interplay between territorial history, socio-political processes, and the evolution of the Sindang language. The findings reveal that the linguistic identity of Sindang is a historical construction shaped by layered social processes, population mobility, and shifting territorial boundaries. This study affirms that the Sindang language functions not only as a means of communication but also as a representation of the enduring cultural identity of the Sindang community.